Economic Rationality of Residents Living in the Area Prone to Merapi Volcanic Disaster - Napsiah, Napsiah; Gunawan, Budhi; Abdoellah, Oekan Soekotjo; Sulaeman, Munandar (Universitas Negeri Semarang, 2017)
The research concerned here was to know the economic rationality of residents who dwelled again in their former village after the eruption of Mount Merapi in 2010 and refused to be relocated by the government. A combined research method, namely, a combination between a qualitative method and a quantitative one, was used to uncover the rationality. The qualitative part of the research was conducted first by deciding informants considered knowledgeable about the matter under research. Then the informants were interviewed in turns decided via snowball sampling. Some secondary data were used to support the qualitative research. As for the quantitative part of the research, it was conducted afterwards by turning members of the households in the village into respondents. The finding of the research is as follows. The residents perceive the disaster not only as a dangerous natural phenomenon but also as an economic blessing because tourists’ visits to the areas suffering from the impact of the disaster enable residents to have activities that have economic value. That economic rationality was what motivated them to return to their village though its condition is categorized by the government as unfit for dwelling.